Peltier System Performance Analysis on Portable Refrigeration Machines: 30 Minute Experimental Case Study - S Chalimah; R Setyobudi; RB Anggoro; A Sadrina; CM Putri; MHB Satria; ES Buana; AR Rizqullah (BIOMEJ, 2024)
This study investigates the performance of Peltier modules, commonly used in portable refrigeration, through the lens of Coefficient of Performance (COP). A portable cooler is constructed using a Styrofoam box, a Peltier module, a heatsink, and a fan. The experiment involves powering the system and recording temperatures on both the cold and hot sides at specific intervals over a 30-minute period.The collected temperature data is then utilized to calculate the COP, a metric that quantifies the system's efficiency by comparing the cooling effect (heat removed) to the electrical energy consumption. This analysis provides valuable insights into the effectiveness of Peltier technology in portable refrigeration applications.The 30-minute timeframe offers a focused case study, allowing for a controlled investigation of the system's performance under steady-state conditions. The study can be further expanded by exploring COP variations at different ambient temperatures, offering a more comprehensive understanding of the system's capabilities in diverse environments.This research contributes to the ongoing exploration of Peltier technology in portable cooling, providing valuable data for optimizing efficiency and design considerations in this growing sector.